2024
DOI: 10.51371/issn.1840-2976.2023.18.1.1
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of Constituent Year effect in Youth Olympic Games: implications for talent identification and development in basketball

Drazen Cular,
Alen Miletic,
Matej Babic

Abstract: Purpose: The Relative Age Effect (RAE) and Constituent Year Effect (CYE) is increasingly recognized as a significant concern in youth sports, especially in basketball where physical traits such as height, arm span, and leg length are emphasized. This focus often eclipses the critical role of age-related variations in talent scouting processes. This study aims to explore the presence and impact of CYE in basketball, with a specific focus on the Youth Olympic Games (YOG). Methods: Utilizing statistical analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…When athletes are allocated to age categories that contain several increments or years in the same age category, e.g., Youth Olympic Games (YOG) sports, the age span varies from 3 years. In these age bands, the effects of the relative age work over a longer period, leading to what is the RAE, also known as the constituent year effect (CYE) [ 11 ]. Given that the literature search yielded no results on CYE in taekwondo articles, we will use the term RAE in this paper.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When athletes are allocated to age categories that contain several increments or years in the same age category, e.g., Youth Olympic Games (YOG) sports, the age span varies from 3 years. In these age bands, the effects of the relative age work over a longer period, leading to what is the RAE, also known as the constituent year effect (CYE) [ 11 ]. Given that the literature search yielded no results on CYE in taekwondo articles, we will use the term RAE in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Given that the literature search yielded no results on CYE in taekwondo articles, we will use the term RAE in this paper. The RAE has been found in many sports and sports categories [ 11 , 12 , 13 , 14 ], but there are also sports where the RAE has not been identified [ 15 ] or in very few cases [ 16 ]. Many studies have found that the RAE mostly exists in male groups of athletes and much less in female groups, as well as a prevalence of RAE in younger categories [ 17 ].…”
Section: Introductionmentioning
confidence: 99%